(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aims of this study are a. to analyze the punching and kicking techniques which score and do not score points, b. to identify the most effective technique used by the karate athletes in order to score points, and c. to be a reference as a training evaluation parameter. Descriptive study with quantitative approach is used in this study. The research sample is the winner in the 75 kg male kumite category at the Olympic Qualification Tournament 2021. The instrument in this study is the stroke and kick techniques employed. The data is presented with descriptive statistics and is analyzed using the SPSS.26 version. The results of this study show that the punching techniques used score more points for the athlete than the kicking techniques. Based on the results, the total use of the punching techniques is 33 times or 60% and it has a 27.27% (counted points) success rate. Meanwhile, the total use of kicking techniques is 22 times or 40% and it has a 0% success rate.